2020
DOI: 10.1080/00223980.2020.1759496
|View full text |Cite
|
Sign up to set email alerts
|

“Me”, “We”, and Materialism: Associations between Contingent Self-Worth and Materialistic Values across Cultures

Abstract: Individuals with high levels of externally contingent self-worth tend to base their self-esteem on factors such as appearance, competitive success, and others' approval. Such tendencies might also elevate people's focus on material possessions. However, cultural moderation of these associations has yet to be explored. A cross-cultural survey among Chinese and Dutch college students examined the link between externally-based contingent self-worth and materialistic values, as well as the mediating roles of need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 97 publications
0
24
0
2
Order By: Relevance
“…Indeed, the love of money has often been seen as a quintessential materialistic trait (Ahuvia, 1992(Ahuvia, , 2015Burroughs and Rindfleisch, 2002;Christopher et al, 2005;Karabati and Cemalcilar, 2010;Richins, 1994;Roets et al, 2006;Tatzel, 2002). Prior research on the antecedents of materialism suggests that the desire for money's security and status-signaling qualities is a common manifestation of materialism (Ahuvia and Wong, 2002;Richins and Chaplin, 2015;Rindfleisch et al, 1997;Rindfleisch et al, 2009;Zhang et al, 2020). For example, Rindfleisch et al (1997) show that individuals raised under conditions of economic insecurity are more likely to develop materialistic values.…”
Section: Brand Love and Materialismmentioning
confidence: 99%
“…Indeed, the love of money has often been seen as a quintessential materialistic trait (Ahuvia, 1992(Ahuvia, , 2015Burroughs and Rindfleisch, 2002;Christopher et al, 2005;Karabati and Cemalcilar, 2010;Richins, 1994;Roets et al, 2006;Tatzel, 2002). Prior research on the antecedents of materialism suggests that the desire for money's security and status-signaling qualities is a common manifestation of materialism (Ahuvia and Wong, 2002;Richins and Chaplin, 2015;Rindfleisch et al, 1997;Rindfleisch et al, 2009;Zhang et al, 2020). For example, Rindfleisch et al (1997) show that individuals raised under conditions of economic insecurity are more likely to develop materialistic values.…”
Section: Brand Love and Materialismmentioning
confidence: 99%
“…The more the culture is individualistic, namely characterized by low interdependence among members, the more wine consumption increases in the analyzed period. This dimension is typically high in modern societies pursuing personal happiness over social obligations and material possession over personal values, with an impact on consumption of goods like wine, which can assume, among others, luxury and status symbol connotations (Ahuvia 2002; Aliyev and Wagner 2018; Zhang et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous literature has suggested that Chinese parents attach great social, moral, and financial importance to children's academic achievements (Chao, 1996;Ng & Wei, 2020). Previous research has also reported a stronger correlation between external contingent self-worth and materialistic values in China than in Western Europe (Zhang et al, 2020). The dual focus on the self and other in the domains of academic performance and material possession might more likely lead to envy, compared with the other domains in our content coding.…”
Section: Themes Present In Mothers' Recalled Experiencesmentioning
confidence: 86%